Production of electronics and photovoltaics using a reel-to-reel process - Graham, A.; Morantz, Paul; Comley, Paul (European Society for Precision Engineering and Nanotechnology, 2016)
Reel to reel manufacturing is a mature technology that involves the passing of a flexible substrate or web continuously through one or more processes. The web is typically much longer than it is wide, and the width in turn is much greater than its thickness. It is a continuous process that results in high output at a low unit cost when compared with other production methods. Historically this has included newspaper printing and textile manufacture, but more recent research is being conducted in developing printed electronics, such as solar cells (Organic Photo-Voltaic or OPV), and wearable tech and flexible screens (Polymer LEDs or PLEDs). These devices consist of up to five layers, with a separate printing or coating process needed for each. Greater accuracy is necessary than for traditional industries and advances are required in three areas: control of the web; measurement and registration of the printed web; and flexible semi-conductor materials. In this paper we present a new methodology to improve printing accuracy by combining an advanced metrology system with an innovative process design.
Keywords: Web tension control; Web lateral control; R2R; Roll-to-roll manufacturing; Organic photovoltaics; Polymer LEDs